Polydopamine-Based Surface Modification for the Development of Peritumorally Activatable Nanoparticles - Gullotti, Emily; Park, Joonyoung; Yeo, Yoon (SPRINGER/PLENUM PUBLISHERS, 2013)
To create poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs), where a drug-encapsulating NP core is covered with polyethylene glycol (PEG) in a normal condition but exposes a cell-interactive TAT-modified surface in an environment rich in matrix metalloproteinases (MMPs). PLGA NPs were modified with TAT peptide (PLGA-pDA-TAT NPs) or dual-modified with TAT peptide and a conjugate of PEG and MMP-substrate peptide (peritumorally activatable NPs, PANPs) via dopamine polymerization. Cellular uptake of fluorescently labeled NPs was observed with or without a pre-treatment of MMP-2 by confocal microscopy and flow cytometry. NPs loaded with paclitaxel (PTX) were tested against SKOV-3 ovarian cancer cells to evaluate the contribution of surface modification to cellular delivery of PTX. While the size and morphology did not significantly change due to the modification, NPs modified with dopamine polymerization were recognized by their dark color. TAT-containing NPs (PLGA-pDA-TAT NPs and PANPs) showed changes in surface charge, indicative of effective conjugation of TAT peptide on the surface. PLGA-pDA-TAT NPs and MMP-2-pre-treated PANPs showed relatively good cellular uptake compared to PLGA NPs, MMP-2-non-treated PANPs, and NPs with non-cleavable PEG. After 3 h treatment with cells, PTX loaded in cell-interactive NPs showed greater toxicity than non-interactive ones as the former could enter cells during the incubation period. However, due to the initial burst drug release, the difference was not as clear as microscopic observation. PEGylated polymeric NPs that could expose cell-interactive surface in response to MMP-2 were successfully created by dual modification of PLGA NPs using dopamine polymerization.
Keywords: INTRACELLULAR DRUG-DELIVERY; CELLULAR UPTAKE; MATRIX METALLOPROTEINASES; MAGNETIC NANOPARTICLES; CANCER-THERAPY; QUANTUM DOTS; TAT PEPTIDE; NANOCARRIERS; PROTEIN; FORMULATION